GRP78-Mediated Signaling Contributes to Axonal Growth Resulting in Motor Function Recovery in Spinal Cord-Injured Mice - Tanie, Yoshitaka; Kuboyama, Tomoharu; Tohda, Chihiro (Frontiers in Pharmacology, 2020)
Promoting axonal growth is essential for repairing damaged neuronal connections and motor function in spinal cord injury (SCI). Neuroleukin (NLK) exerts axonal growth activity in vitro and in vivo, but the mechanism remains unclear. This study reveals that the 78-kDa glucose-regulated protein (GRP78) is a NLK neuronal receptor that contributes to recovery from SCI. Binding and immunoprecipitation assays indicated that NLK binds to GRP78. Pretreatment to cultured neurons with a GRP78-neutralizing antibody suppressed NLK-induced axonal growth. Blocking cell surface GRP78 inhibited neuronal NLK-induced Akt activation. Treatment with an Akt inhibitor suppressed NLK-induced axonal growth. Continuous administration of NLK into the lateral ventricle of SCI mice increased axonal density in the injured region and restored motor function, which was not observed when NLK was simultaneously administered with a GRP78-neutralizing antibody. These results indicate that GRP78 regulates the NLK-induced axonal growth activity; NLK-GRP78 signaling promotes motor function recovery in SCI, presenting as a potential therapeutic target.